Disruptive behaviour in an Ontario population of complex continuing care patients using the Minimum Data Set (2.0) - Stewart, Stacey (My University, 2005)
The purpose of this study was to examine disruptive behaviour within a population of complex continuing care patients, and to identify the risk factors for such behavior. Data obtained from 14,023 residents upon admission into complex continuing care facilities were analyzed using the Minimum Data Set (2.0). Disruptive behavior was measured by the Disruptive Behaviour Scale developed by Stones, Stewart and Kirkpatrick (2003). The predictors of disruptive behaviour examined included demographic characteristics (gender, age), psychiatric diagnosis (anxiety, dementia, depression) use of medications (antianxiety, antidepressants, antipsychotics), restraint, functional status of the resident (Activities of Daily Living, recent and lasting delirium, incontinence, cognitive impairment), visual limitations, oral/dental status, pain, depressed affect, and withdrawal. The strongest predictors of disruptive behaviour included dementia, antipsychotic medication, bladder incontinence, tooth loss, depressed affect, recent and non recent delirium, withdrawal, restraint, vision impairment, antianxiety medication, activities of daily living, frequency of pain, and gender. The results are discussed in relation to proper detection and treatment of frequent conditions in care facilities that may help to reduce disruptive behaviour.
Keywords: Disruptive behaviour (elderly patients); Geriatric nursing (Psychological aspects); Nursing home patients (Psychology); Long term care